Experimental study on process parameter to reduce wrinkling in sheet metal forming - Nik Muhd Hazwan, Nik Abd Aziz (2013)
Deep drawing operations are crucial for metal forming operations. Obtaining a defect free final product with the desired mechanical properties is very important for fulfilling the customer expectations and market competitions. Flange wrinkling is one of the fatal and most frequent defects that must be prevented. This study focuses on understanding the phenomenon of flange wrinkling and prevention method that can be applied to avoid the flange wrinkling defect. MINITAB software was used to analyze parameters in order to understand level of flange wrinkling and effect in experiments against of sheet metal. Model of a cup are used to investigate with different thickness but the blank holder force depend on spring. This process also depends on calculation, and the material that we use is mild steel. Flange wrinkling instability is illustrated in energy diagrams of the process. Effect of anisotropy on flange wrinkling is also discussed by comparing with using different thickness. Besides experimental which is conducted as conventional deep drawing operation by a hydraulic press, numerical analysis verification is also performed and this yields will show the ability to understand the effect of blank thickness on flange wrinkling formation through experimental and numerical analysis. The wave formations different sized of blanks with same metals are illustrated.